2001
DOI: 10.1083/jcb.153.4.785
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphin Mediates Mammary Luminal Morphogenesis through Control of C/EBPβ

Abstract: We have shown previously that epimorphin (EPM), a protein expressed on the surface of myoepithelial and fibroblast cells of the mammary gland, acts as a multifunctional morphogen of mammary epithelial cells. Here, we present the molecular mechanism by which EPM mediates luminal morphogenesis. Treatment of cells with EPM to induce lumen formation greatly increases the overall expression of transcription factor CCAAT/enhancer binding protein (C/EBP)β and alters the relative expression of its two principal isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 79 publications
2
76
0
Order By: Relevance
“…However, in cells where C/EBPb-2 is the only or predominant transactivator isoform, C/EBPb-3 overexpression may antagonize growth and invasion. Indeed, Hirai et al (2001) found that moderate levels of LIP expression in SCp2 mouse mammary epithelial cells, which express LAP (C/EBPb-2), promoted luminal morphogenesis, whereas high expression of LIP led to apoptosis. With regard to human breast tumor tissue, Zahnow et al (1997) reported that highgrade, invasive human mammary carcinomas exhibit high levels of LIP (p20) or C/EBPb-3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cells where C/EBPb-2 is the only or predominant transactivator isoform, C/EBPb-3 overexpression may antagonize growth and invasion. Indeed, Hirai et al (2001) found that moderate levels of LIP expression in SCp2 mouse mammary epithelial cells, which express LAP (C/EBPb-2), promoted luminal morphogenesis, whereas high expression of LIP led to apoptosis. With regard to human breast tumor tissue, Zahnow et al (1997) reported that highgrade, invasive human mammary carcinomas exhibit high levels of LIP (p20) or C/EBPb-3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Syntaxins are the target membrane soluble N-ethylmaleimide-sensitive factor attachment protein receptors (t-SNARE) that mediate intracellular vesicle targeting and fusion. 6,37,38 Among syntaxin members, epimorphin (syntaxin-2) is the only one reported to exert an effect extracellularly as an epithelial morphogen. To preliminarily analyze the possible roles of other syntaxin members in renal fibrosis, we analyzed the expression of mRNA for syntaxin1a, which shows a very high level of sequence similarity but has no activity as a morphogen, 39 by real-time RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that epimorphin has morphogenetic effects on multiple epithelial tissues, including those of skin, hair follicle, lung, intestine, mammary gland, pancreas, gall bladder and liver. [4][5][6][7][8][9][10] In addition, several investigators have reported changes in the distribution of epimorphin-positive cells in inflammatory diseases of the lung and liver. [11][12][13][14] Epimorphin not only regulates morphogenesis but also functions as a mesenchymal regulator of epithelial repair.…”
mentioning
confidence: 99%
“…Human Sox9 expression vector was described before (35). Human Col2A1 promoter construct and C/EBP expression vectors were the kind gifts provided by the following: 4-kb promoter and enhancer construct spanning Ϫ577 to ϩ3426 bp of human COL2A1 in the pGL2-basic vector was obtained from Dr. Mary B. Goldring (36,37); human C/EBP-full-length in the pCDNA3 vector was from Dr. Erika Crouch (38); the rat pCI-neo-LIP was from Dr. Cynthia A. Zahnow (39); the rat pCMV-LAP was from Dr. Mina Bissell (40); and the rat pMSV-C/EBP␦ was from Dr. Alan Friedman (41). The empty expression vectors were made by excision of cDNAs from the corresponding C/EBP expression vectors.…”
mentioning
confidence: 99%